2011
DOI: 10.1016/j.ceca.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

High levels of synaptosomal Na+–Ca2+ exchangers (NCX1, NCX2, NCX3) co-localized with amyloid-beta in human cerebral cortex affected by Alzheimer's disease

Abstract: Synaptosomal expression of NCX1, NCX2, and NCX3, the three variants of the Na+-Ca2+ exchanger (NCX), was investigated in Alzheimer’s disease parietal cortex. Flow cytometry and immunoblotting techniques were used to analyze synaptosomes prepared from cryopreserved brain of cognitively normal aged controls and late stage Alzheimer’s disease patients. Major findings that emerged from this study are: (1) NCX1 was the most abundant NCX isoform in nerve terminals of cognitively normal patients; (2) NCX2 and NCX3 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…This cellular model is complementary to the BHK-cellular approach. Indeed, BHK-WT cells do not constitutively expressed any NCX isoform, BHK-NCX3 cells are genetic engineered cells to solely expressed NCX3-specific brain isoform whereas wild-type VMC neurons express NCX1, NCX2 and NCX3 isoforms (Canitano, 2002, Linck, 1998, Minelli, 2007, Nicoll, 1996, Sokolow, 2011). Due to the lack of selective NCX3 inhibitor, we opted to investigate the role of ziram induced DA toxicity in VMC neurons isolated from NCX3 knock-out mice (Molinaro, 2008, Molinaro, 2011, Pannaccione, 2012, Sokolow, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cellular model is complementary to the BHK-cellular approach. Indeed, BHK-WT cells do not constitutively expressed any NCX isoform, BHK-NCX3 cells are genetic engineered cells to solely expressed NCX3-specific brain isoform whereas wild-type VMC neurons express NCX1, NCX2 and NCX3 isoforms (Canitano, 2002, Linck, 1998, Minelli, 2007, Nicoll, 1996, Sokolow, 2011). Due to the lack of selective NCX3 inhibitor, we opted to investigate the role of ziram induced DA toxicity in VMC neurons isolated from NCX3 knock-out mice (Molinaro, 2008, Molinaro, 2011, Pannaccione, 2012, Sokolow, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in NCX2 deficient mice implied that NCX2 is important for cognitive function (Jeon, 2003). We produced NCX3 knockout mice and showed that NCX3 plays a significant role in cognition (Molinaro et al, 2011), in oligodendrocyte differentiation (Boscia et al, 2013), in amyloid-beta pathology (Pannaccione et al, 2012, Sokolow et al, 2011) and is protective against ischemic damage (Cross et al, 2009, Jeffs et al, 2008, Molinaro et al, 2013, Molinaro et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Three different isoforms of the NCX (NCX1, NCX2 and NCX3) have been characterized, cloned and detected in various tissues, including the central nervous system (Philipson and Nicoll, 1997; Quednau et al, 1997; Papa et al, 2003; Lytton, 2007). The NCX has been implicated in the pathophysiology of various neurological conditions, including Alzheimer’s disease (Bi et al, 2012; Sokolow et al, 2011), ischemia (Pignataro et al, 2004; Lee et al, 2005; Boscia et al, 2006), hypoxia (Secondo et al, 2007) and Parkinson’s disease (Ago et al, 2011). Although the role of the NCX in the pathogenesis of seizures and epilepsy remains poorly understood, we have reported that inhibition of Ca 2+ influx via NCX activity in the reverse mode reduced the incidence of pilocarpine-induced limbic seizures and status epilepticus (Martinez and N’Gouemo, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SLC8A1/NCX1 is widely expressed in most tissues although it is most abundant in the heart, while expression of SLC8A2/NCX2 is restricted to the brain and spinal cord and SLC8A3/NCX3 expression is restricted to the brain and skeletal muscle 74). The Na + /Ca 2+ exchanger is also expressed in immune cells, including SLC8A1/NCX1 and SLC8A3/NCX3 which are expressed in both macrophages and monocytes 75).…”
Section: Genetic Synergismmentioning
confidence: 99%